25 year old kickboxer with progressive proptosis - Brun, Scott C.; Rubin, Peter A. D. (Digital Journal of Ophthalmology, 1997)
A 25-year-old man complained of mildly painful "swelling out" of his left eye over the previous 2 months. He denied visual blurring, diplopia, or a history of direct trauma. He was started on a course of oral antibiotics for presumed sinusitis, which failed to halt or reverse the process.